Desarrollo socio-afectivo para la atención de niños con trastorno espectro autista - Escobar Delgado, Sonnia Fabiola (2023)
The research carried out on the socio-affective development for the attention of children with Autism Spectrum Disorder whose problem refers to the difficulties that high school teachers have in providing the required attention in how to strengthen the socio-affective development in students with ASD. , the proposed objective is: to analyze the attention of the teacher in the socio-affective development of children with Autism Spectrum Disorder of the Américo Vespucio Educational Unit. In the theoretical framework, through the search for information related to each of the research variables, the importance of socio-affective development for the work of children with ASD has been supported, which have been taken from different investigative sources, in addition This research has a mixed approach, a combination between the quantitative and the qualitative, in the quantitative aspect a survey was presented that was applied to the teachers and in the qualitative aspect the interview with managers, DECE and the classroom observation directed to the teacher's work in the school were applied. classroom with students who present ASD, it is of a descriptive and field type, empathic and theoretical methods were also part, the population and sample in the investigation were teachers, managers, DECE and high school students. The corresponding analysis of the information collected demonstrated the difficulties that teachers have in attending to and improving the socio-affective development of students with ASD and with the application of the instruments it was possible to determine that teachers need to be trained for a more efficient attention to said students, for this reason it is presented as a solution proposal in which an activity guide for teachers was designed to strengthen the socio-emotional development of children with ASD.